2022
DOI: 10.1002/hed.27026
|View full text |Cite
|
Sign up to set email alerts
|

Management of oral feeding following total laryngectomy around the world: YO‐IFOS international study

Abstract: Background: To analyze worldwide practices regarding the initiation of oral feeding after total laryngectomy (TL). Methods: Online survey.Results: Among the 332 responses received, 278 from 59 countries were analyzed. Our results showed that 45.6% of respondents started water and 45.1% started liquid diet between postoperative days 7 and 10. Semi-solid feeds were initiated between days 10 and 14 for 44.9% of respondents and a free diet was allowed after day 15 for 60.8% of respondents. This timing was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Of note, the patients in our study did not have an early oral intake of a clear fluid, despite it being shown to reduce the occurrence of PCF 20 . However, the refeeding method we used was similar to the refeeding practice of many teams 21 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, the patients in our study did not have an early oral intake of a clear fluid, despite it being shown to reduce the occurrence of PCF 20 . However, the refeeding method we used was similar to the refeeding practice of many teams 21 …”
Section: Discussionmentioning
confidence: 98%
“…20 However, the refeeding method we used was similar to the refeeding practice of many teams. 21 Our study population is representative of patients managed by TL, with a large number having received prior medical treatment, for example chemoradiotherapy (46%). The study also confirms the important consequences of PCF for the patients such as longer hospital stay and delayed return to oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…The best timing for VFSS performance is a question that remains unanswered in the current literature. 19 Our study focused on a single post-operative protocol; therefore it could not compare various timings. While the time of salivary leak formation after TL is not accurately known, their occurrence before postoperative day 5 was exceptional in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The best timing for VFSS performance is a question that remains unanswered in the current literature 19 . Our study focused on a single post‐operative protocol; therefore it could not compare various timings.…”
Section: Discussionmentioning
confidence: 99%